The Role of Hygienic Education in the System Primary Prevention of Dental Diseases (Eurasian Research Bulletin, 2023)
The review presents an analysis of data on the prevalence, the intensity of dental caries and the level of oral hygiene in children and adolescents in various countries of the world, as well as modern methodological approaches to hygienic education in organized general educational children's groups and individually